Knowledge and practices of primary health care physicians regarding updated guidelines of MERS-CoV infection in Abha city - Al-Amri, Saad (J Family Med Prim Care, 2019)
BACKGROUND: Human coronaviruses (hCoV) usually cause mild to moderate upper respiratory tract illnesses. The novel coronavirus (nCoV), or Middle East respiratory syndrome coronavirus (MERS-CoV), is a particular strain different from any other known hCoV with the possibility of human and also zoonotic transmissions. The aim of the study to assess primary health care (PHC) physicians’ knowledge and adherence regarding Saudi Ministry of Health guidelines regarding MERS-CoV. MATERIALS AND METHODS: A cross-sectional study design was followed to include 85 PHC physicians in Abha city. An interview questionnaire has been designed by the researcher that was used to assess knowledge and practices of PHC physicians regarding diagnosis and management of MERS-CoV. It includes personal characteristics, the MERS-CoV knowledge assessment questionnaire, and practices related to adherence toward guidelines regarding MERS-CoV. RESULTS: PHC physicians’ knowledge gaps regarding MERS-CoV included protected exposure (32.9%), highest seasonal incidence of MERS-CoV in Saudi Arabia (60%), relation between incidence of MERS-CoV and overcrowding (62.4%), case fatality of MERS-CoV cases (63.5%), and collecting specimens from MERS-CoV patients (64.7%). The knowledge of PHC physicians about MERS-CoV was poor among 5.9%, good among 63.5%, and excellent among 30.6%. Personal protective equipment to be used when seeing suspected cases of MERS-CoV infection were mainly the mask (94.1%), gloves (78.8%), the gown (60%), goggles (31.8%), and the cap (22.4%). All participants stated that the most important standard precaution that should be applied when seeing a case of MERS-CoV infection is hand washing, whereas 97.6% stated that the most important respiratory precaution to prevent transmission of respiratory infections in PHC setting when seeing a case of MERS-CoV infection is masking and separation of suspected MERS-CoV patients, and 81.2% stated that upon exit from the room of a MERS-CoV patient, the physician should remove and discard personal protective equipment. PHC physicians’ knowledge about MERS-CoV differed significantly according to their nationality (P = 0.038), with non-Saudi physicians expressing higher percent of excellent knowledge than Saudi physicians (40% and 20%, respectively). Those who attended continuing medical education (CME) activities had significantly higher percent of excellent knowledge than those who did not attend a CME activity (55.6% and 23.9%, respectively, P = 0.011). PHC physicians’ knowledge did not differ significantly according to their age, gender, qualification, experience in PHC, and practice-related adherence to guidelines. PHC physicians’ practice-related adherence to guidelines about MERS-CoV differed significantly according to their position (P = 0.035), with specialists having the highest percent of excellent practice (13%). CONCLUSIONS: There are knowledge gaps among PHC physicians in Abha city, and their practice is suboptimal regarding MERS-CoV infection. Less than one-fourth of PHC physicians attend CME activities about MERS-CoV infection. However, significantly less practice-related adherence to guidelines are associated with Saudi PHC physicians, those who did not attend a related CME activity, and MBBS qualified physicians’ general practitioners. To increase awareness, more CME activities related to MERS-CoV infection management needs to be organized.